Effects of tumour necrosis factor-α on BrdU incorporation in cultured human enterocytes - J. McDevitt; C. Feighery; C. O'Farrelly; G. Martin; D. G. Weir; D. Kelleher (Hindawi Limited, 1995)
Bromodeoxyuridine incorporation is a useful method for studying the pattern of DNA synthesis in proliferating cells. The distribution pattern of incorporated BrdU in villus enterocytes of duodenal explants was analysed after exposure to TNFα in organ culture. TNFα caused a consistent, low level uptake of BrdU in the portion of the nucleus close to the nuclear membrane, this pattern was absent from the control cultures. As these epithelial cells are terminally arrested in G0, the BrdU incorporation was thought not to be due to S phase DNA synthesis, but rather a response to the cytotoxic influence of TNFα. Microtitre plate proliferation assays of cell density and DNA synthesis were devised to study the effects of TNFα on confluent monolayers of the human foetal jejunal cell line I407 and the mouse fibrosarcoma cell line L929. Both cell lines showed a similar response to TNFα. Exposure to TNFα alone did not reduce cell numbers but did cause a significant increase in DNA synthesis (p < 0.05). When cycloheximtde was added in tandem with TNFα there was a significant reduction in cell number (p < 0.001) and level of DNA synthesis (p < 0.01) indicative of cell death. The DNA of cells exposed to TNFα and cycloheximide was fragmented when viewed on an electrophoresis gel. The results show that BrdU incorporation might be a good indicator of damage to the DNA of cells after cytotoxic insult. TNFα may be responsible for villus enterocyte damage in enteropathies such as coeliac disease and GVHR of the small bowel.